TINJAUAN FIQH SIYASAH TERHADAP PERAN POLISI PAMONG PRAJA PADA MASA PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT - Muhajir, Muhajir; Hamiyuddin, Hamiyuddin (Datuk Sulaiman Law Review (DaLRev), 2023)
This study is entitled a review of fiqh siyasah on the role of civil service police during the time of imposing restrictions on community activities (studies on the civil service police unit of Palu City). The problems are 1). What is the review of fiqh siyasa on the role of civil service police during the time when restrictions on community activities were imposed in the city of Palu? 2). What obstacles arise in carrying out the duties and roles of the Civil Service Police during the implementation of restrictions on community activities in the city of Palu? And aims to: 1). To understand the fiqh siyasa review of the role of the civil service police during the time when restrictions on community activities were imposed in the city of Palu. 2). To understand the obstacles that arise in executing tasks and the role of civil service police when implementing restrictions on community activities in Palu. This study uses an interdisciplinary approach to examine a topic/issue, where communication, collaboration, and integration occur, starting from definitions, objectives, processes, and data collection to analysis and conclusions. The subjects in this study consisted of secretaries and heads of public protection. Meanwhile, the object of this study is a fiqh siyasah review of the role of civil service police during the time when restrictions on community activities were imposed. A review of siyasa fiqh on the role of the Polisi pamong Praja during the time when restrictions on community activities were imposed in the city of Palu is in accordance with the principles of siyasa fiqh. The efforts of thePolisi Pamong Praja helped raise awareness and provide understanding to the public so that the city of Palu is free from Covid-19.The conclusion from the results of the study is that cooperation between authorities such as Polisi Pamong Praja, TNI, Polri, transportation service and the community can help the city of Palu be free from the spike in the increase in exposure to Covid-19 when restrictions on community activities were imposed. Suggestions from this study are that the municipal police unit in Palu City needs to improve its human resources so that it can maximize the tasks carried out during the implementation of restrictions on community activities and take a closer approach to the people of Palu City so that they prioritize discipline and comply with health protocols to achieve this. Palu city that is healthy and free of covid-19.